(untitled) (International Journal of Food and Nutritional Sciences, 2019)
Cold stress is considered as a co-morbid factor in diabetic subjects which causes reduced glucose tolerance and an increase in both corticosterone and glycaemia resulting in oxidative stress and damage of body tissues. This study aimed to address the changes in female reproductive organs somatic index in relation to glucose levels and feeding indices in diabetics exposed to cold stress and also evaluating the ameliorative efficacy of Tribulus terrestris fruit (TTF) and Mesua ferrea flower (MFF) extracts to tackle the insults